The Analysis Study of Efficacy, Effectiveness, and Clinical Risk of Tramadol as Treatment of Premature Ejaculation : A Comprehensive Systematic Review - Nugraha, Dhimas Mohammad Fajar; Akmalia, Tsalitsa Laili (The Indonesian Journal of General Medicine, 2024)
Background: Premature ejaculation is a common sexual dysfunction affecting 20%-30% of men. Understanding the effectiveness and potential dangers of tramadol in treating premature ejaculation can help develop efficient treatment protocols. Methods: In accordance with the PRISMA 2020 principles, this systematic review focused specifically on comprehensive English literature published from 2013 to 2024. Result: The study examined over 2000 papers from respectable sources such as Science Direct, SagePub, and PubMed. Following the decision to subject eight publications to further scrutiny, a comprehensive examination of the complete body of literature was conducted. Conclusion: Tramadol, an analgesic derived from opioids, effectively suppresses premature ejaculation (PE) and enhances sexual satisfaction during sexual intercourse. Nevertheless, the efficacy and safety of its use in treating PE are still a subject of discussion due to a lack of solid empirical evidence. Additional investigation is required to ascertain the effectiveness of the medication and its possible adverse effects.